Mechanical, fracture-deformation, and tribology behavior of fillers-reinforced sisal fiber composites for lightweight automotive applications - Miniappan Pethampalayam Karuppanan; Marimuthu Sivagnanam; Kumar Selvan Dharani; Gokilakrishnan Gopal; Sharma Shubham; Li Changhe; Dwivedi Shashi Prakash; Abbas Mohamed (Reviews on Advanced Materials Science, 2023)
The main focus of this study is on the effects of fly ash, basalt powder, and tungsten carbide (WC) on the mechanical (tensile strength, flexural strength, impact strength, and Shore D hardness) and tribology behavior of sisal fiber-reinforced composites. Using epoxy resin, the fillers (5–10 wt% of each) were mixed with sisal fiber and resin (30 wt%). A tensile strength of 86.3–112.2 MPa was observed with the addition of fly ash, basalt powder, and WC fillers. The tensile strength of S2 composite (basalt powder + epoxy resin) was 33.63% higher than that of composite without fillers. The flexural strength of S5 composite (basalt powder + WC) was found to be 166.4 MPa, which is nearly 19.95% higher than the composite without filler. The fly ash with WC (S4) and basalt powder (S5) composite showed similar impact strength (5.34 J·m−2), which was nearly 62% greater than the composites without filler. The superior hardness was noticed in S5 composite compared to all other filler-added composites. The least wear rate was noticed in S3 (WC) composites irrespective of all the loading conditions. The hybridization of fillers also enhanced the mechanical properties of sisal fiber–reinforced composites. However, single filler–reinforced composite (WC) improved the wear resistance compare to hybrid filler–reinforced composites. The inclusion of filler increases the load-carrying capability and adhesion, as determined by scanning electron microscope. The river-like pattern confirms that S2-composite failure was dominated by ductile. The least wear debris and grooved surfaces were results higher wear resistance in the hybrid filler–reinforced composites.